Between malocas and malones: Indigenous resistance through violence as a response to colonial violence in 17-century - Farías Rojas, Gabriel Arturo (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The objective of this article is to reflect on Malocas and Malones as the dynamics of a micro-war in the frontier between the Tolten River and the Chacao Channel. Whereas the Spanish were replicating the old medieval methods used against Moors in their frontier dynamics, indigenous peoples responded out of resentment and wrath. The idea of it was to dissuade them from expanding the frontier and to resist against the endless war before the Great Indigenous Rebellion in 1598. Finally, comparing Malones to Comanches’s raids in North America will prove useful to understanding both resistance and colonizing ambitions.